Anesthesia and Long-term Oncological Outcomes: A Systematic Review and Meta-analysis. (March 2021) - Chang, Chun-Yu; Wu, Meng-Yu; Chien, Yung-Jiun; Su, I-Min; Wang, Shih-Ching; Kao, Ming-Chang
Abstract : BACKGROUND: Whether propofol elicits a survival benefit over volatile anesthetics during cancer surgery remains inconclusive. The primary aim of this systematic review and meta-analysis is to compare the effects of propofol-based total intravenous anesthesia (TIVA) with any volatile anesthesia on long-term oncological outcomes. The secondary aim is to compare propofol-based TIVA with specific volatile agents on long-term oncological outcomes. METHODS: We searched PubMed, Embase, Scopus, Web of Science, and Cochrane Library from inception through March 3, 2020. Randomized control trials and observational studies that compared the effects of propofol-based TIVA and volatile anesthesia on long-term oncological outcomes, which also reported hazard ratios (HR) as effect estimates, were considered eligible for inclusion. Using the inverse variance method with a random-effects model, HR and 95% confidence intervals (CI) were calculated. Trial sequential analysis was incorporated to test if the results were subject to a type I or type II error. RESULTS: Nineteen retrospective observational studies were included. Patients who received propofol-based TIVA during cancer surgery were associated with significantly better overall survival than those who received volatile anesthesia (HR = 0.79, 95% CI, 0.66-0.94, P = .008, I 2 = 82%). In contrast, no statistically significant difference was observed in recurrence-free survival between patients who received propofol-based TIVA and volatile anesthesia during cancer surgery (HR = 0.81, 95% CI, 0.61-1.07, P = .137, I 2 = 85%). In the subgroup analysis by different volatile anesthetics, patients who received propofol-based TIVA were associated with better overall survival than those who received desflurane (HR = 0.54, 95% CI, 0.36-0.80, P = .003, I 2 = 80%). In contrast, there was no statistically significant difference in overall survival between patients who received propofol-based TIVA and those who received sevoflurane (HR = 0.92, 95% CI, 0.74-1.14, P = .439, I 2 = 70%). In the trial sequential analysis of overall survival, the cumulative Z curve reached the required heterogeneity-adjusted information size and crossed the traditional significance boundary. In contrast, in the trial sequential analysis of recurrence-free survival, the cumulative Z curve did not cross the traditional significance boundary. However, the required heterogeneity-adjusted information size has not yet been reached. CONCLUSIONS: Propofol-based TIVA is generally associated with better overall survival than volatile anesthesia during cancer surgery. Further large-scaled, high-quality randomized control trials are warranted to confirm our findings.